Layanan Informasi Berbantuan Statistik untuk Meningkatkan Pemahaman Terhadap Covid-19 Serta Melatih Berliterasi Numerasi - Aditya Jakti, Yang Gustida (Jurnal Didaktika Pendidikan Dasar, 2022)
Education is a medium of transfer of knowledge which is very important for sustain a nation. The Covid-19 pandemic that occurred in early 2020 made the concept hampered. The learning from home situation that suddenly makes Covid-19 information cannot be conveyed optimally to students. Through the Covid-19 statistical-assisted information service, the concept of understanding Covid-19 and numeracy literacy can be done at one time. This type of research is descriptive research using a qualitative approach. The research subjects were students of grades 8H and 8I totaling 63 students. Data collection methods used are questionnaires, interviews, and observations. Questionnaire data obtained through google form showed that 98.4% of students stated that they understood the information conveyed better. Based on interviews, students stated that the delivery of information using statistical data was more interesting and clear than accessing it independently. During the activity, students seemed more interested and paid close attention to the information. Based on the results obtained, the implementation of Covid-19 statistical-assisted information services can be said to have succeeded in increasing students' understanding of Covid-19 and training students in numeracy literacy during the pandemic.